Apakah yang Memiliki Akun Roleplay di Media Sosial X Kesepian? (Studi Literasi Dukungan Sosial dan Fear of Missing Out) - Fatima Azzahra; Cempaka Putrie Dimala; Dinda Aisha (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2025)
Loneliness among social media users is often associated with dissatisfaction with real-life social relationships, which may encourage individuals to seek alternative forms of connection in virtual environments. One such phenomenon is the use of roleplay accounts on the social media platform X (formerly Twitter), where users construct virtual relationships such as romantic partners, families, or friendship networks. This study aimed to analyze the influence of perceived social support and fear of missing out (FoMO) on loneliness among roleplay account users. A quantitative research approach with a correlational design was employed. The participants consisted of 385 roleplay account users on social media platform X, selected using the snowball sampling technique. Data were collected using standardized instruments, namely the UCLA Loneliness Scale (Version 3), the Multidimensional Scale of Perceived Social Support (MSPSS), and the Fear of Missing Out Scale (FoMOS). Data analysis was conducted using multiple regression analysis to examine both partial and simultaneous effects of the independent variables on loneliness. The results indicated that social support and fear of missing out each had a significant partial effect on loneliness, with a significance value of p = 0.000 (p < 0.05). Furthermore, social support and FoMO simultaneously influenced loneliness, accounting for 48% of the variance. Higher levels of perceived social support were associated with lower levels of loneliness, while higher levels of FoMO were associated with increased loneliness. These findings suggest that although roleplay communities may provide a sense of belonging, psychological factors such as social support and FoMO remain critical determinants of loneliness. This study highlights the importance of strengthening perceived social support and managing FoMO to reduce loneliness among roleplay account users in online social environments.